The affective atmospheres of nationalism - Stephens, Angharad Closs (Cultural geographies, 2016)
What would it mean to understand nationalism as an atmosphere? This article makes a theoretical contribution to cultural geographical works on ‘affective atmospheres’ as well as to critical approaches to the study of nationalism by addressing this question. It examines how nationalism operates affectively and atmospherically through a discussion of the event of the London 2012 Olympic Games and the ‘happy atmospheres’ of being together that circulated in the course of those Games. The key claim of the article is that addressing the nation’s affective, emotional and atmospheric resonances is critical for understanding how nationalism endures and, furthermore, how it appears especially difficult to critique. As such, the article points to different ways in which thinking about nationalism as an ‘affective atmosphere’ builds upon the notion of ‘everyday nationalism’ but also takes it further by inviting an attentiveness to the different tonalities and intensities of nationality and shifting the focus from a subject identity or bounded community to the question of how affective forces congeal around particular objects and bodies and echo as part of an assemblage. Finally, this article makes a contribution to debates around the relationship between affect, atmosphere and politics by asking how national affective atmospheres might be resisted.